Perancangan Jig Machining untuk Perbaikan Electroda ST-03 - Sanurya Putri Purbaningrum; Arif Muttaqin; Fredy Sumasto; Edwin Sahrial Solih (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The automotive industry in Indonesia is one of the priority industrial sectors that is developing quite rapidly. The automotive component production process in industry generally includes the molding process, welding process, assembly process, and automotive component quality control process. During the welding process,the ST-03 electroda used by PT ST-03 electroda repairs were carried out using a CNC Milling machine. The electroda repair process is carried out one by one with a total time of 120 minutes or 2 hours per day. The large amount of time required for the repair process makes loading parts hampered. Therefore, a jig machining design was carried out to speed up the electroda repair process. The ST-03 jig machining material used is SS 400 iron. The product design was carried out using CAD software and then simulated using CAM. The simulation results show that the use of jig machining can reduce production time by 98%or 118 minutes. This is because in one set up you can repair 20 electrodas so that in 1 day you only need to do 3 set ups. The profit obtained from using the ST-03 jig machining electroda is 166,500,000 rupiah per year.